Translation and scientific terminology: a corpus-based multilingual study - Ji, M (2010)
It is well known that the establishment of modern scientific language in the late nineteenth century was instrumental in the making of China's and Japan's early modern scientific identity. The current study aims to offer an original empirical investigation of early modern Chinese scientific terminology from a cognitive and functional perspective, which has been rarely explored before. Through a detailed corpus-based linguistic investigation, the present study probes the complex historical process of cross-cultural and cross-linguistic scientific exchange between the West and China and Japan in the late nineteenth century. The new insights brought about by the novel use of statistical methods point to potentially prolific directions for future research in contrastive historical linguistics and science history.